2001
DOI: 10.1046/j.1365-2168.2001.01671.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aspirin on early allograft thrombosis and chronic allograft nephropathy following renal transplantation

Abstract: Aspirin reduced the rate of early graft thrombosis of renal transplants in this series but did not improve renal function or graft survival. A trend towards a lower rate of chronic allograft nephropathy was noted with aspirin treatment. These findings require confirmation in a prospective randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 27 publications
3
34
0
1
Order By: Relevance
“…Some centres have selected aspirin as their preventative therapy [14,15]. A retrospective analysis of 475 adult renal transplant recipients between 1985 and 1991 and from 1991 to 1997 (aspirin prophylaxis was introduced in 1991) [14] showed a significant reduction in RVT from 5.6% to 1.2% in those who received low-dose aspirin prophylaxis.…”
Section: Discussionmentioning
confidence: 98%
“…Some centres have selected aspirin as their preventative therapy [14,15]. A retrospective analysis of 475 adult renal transplant recipients between 1985 and 1991 and from 1991 to 1997 (aspirin prophylaxis was introduced in 1991) [14] showed a significant reduction in RVT from 5.6% to 1.2% in those who received low-dose aspirin prophylaxis.…”
Section: Discussionmentioning
confidence: 98%
“…Aspirin was shown to reduce the rate of early graft thrombosis; however, it did not improve graft function or survival. 15 Grotz and associates showed that lowdose aspirin therapy improved graft function and survival. 17 However, their study had a significant limitation; the mean time to start of aspirin was 2.64 years after transplant, and aspirin therapy only covered 50% of the overall graft survival time.…”
Section: Discussionmentioning
confidence: 99%
“…Also the immunosuppressive regimen in that study was cyclosporine, and patients did not receive induction therapy with basiliximab or antithymocyte globulin. 15 In our study, recent immunosuppressive protocols were used; all patients received induction therapy with basiliximab or antithymocyte globulin, and most patients were on tacrolimus as maintenance therapy. Aspirin was started from day 1 posttransplant, and long-term therapy covered the whole period analyzed posttransplant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations